PSYCHOGRAPHIC CULTURAL FACTORS – TRIGGERS IN CONSUMER DECISION MAKING (International Journal of Food and Nutritional Sciences, 2022)
Psychographic cultural factors play a significant role in shaping consumer decision making. This study aims to explore the triggers associated with psychographic cultural factors that influence consumer behavior and decision making. By examining the intersection of psychology and culture, this research seeks to understand how individual personality traits, values, beliefs, and lifestyles interact with cultural norms and social influences to impact consumer choices.